A The Composition and content of fatty acid, lipid classes of two octopus species: \(Amphioctopus neglectus\) and \(Cistopus indicus\) from Ha Long bay, Quang Ninh province, Vietnam - Dinh Thi, Ha; Doan Lan, Phuong; Pham Van, Chien; Nguyen Van, Quan; Nguyen, Duc The (Vietnam Journal of Marine Science and Technology, 2023)
The fatty acid compositions of the lipids of two octopus species (Amphiotopus neglectus and Cistopus indicus) were investigated. The composition and content of fatty acids of two octopus samples were analyzed using a GC-MS. The percentages of the lipid classes in total lipid were determined based on the image analysis program Sorbfil TLC Videodensitometer DV, Krasnodar, Russia. The highest content of docosahexaenoic acid (DHA) (from 20.65% to 34.56% of total fatty acids) in the lipids of both species was revealed, followed by the content of eicosapentaenoic acid (EPA), palmitic acid, and arachidonic acid (AA) in the ranges (12.76–21.54%; 12.23–14.96%; and 8.99–17.26% of total fatty acids, respectively). The content of unsaturated fatty acids did differ between males and females of the two species studied. However, these differences are few and can be explained by the timing of their breeding seasons. The fatty acid composition of the fats from both investigated octopus species permits their use as food with nutritional value, and the production of bioactive additives.